Diverse Aquatic Adaptations in Nothosaurus spp. (Sauropterygia)—Inferences from Humeral Histology and Microanatomy - Klein, Nicole (PLoS One, 2016)
Mid-diaphyseal cortical bone tissue in humeri of Nothosaurus spp. consists of coarse parallel-fibered bone, finer and higher organized parallel-fibered bone, and lamellar bone. Vascular canals are mainly arranged longitudinally and radially in a dominantly radial system. Blood vessels are represented by simple vascular canals, incompletely lined primary osteons, and fully developed primary osteons. Nothosaurus spp. shows a variety of diaphyseal microanatomical patterns, ranging from thick to very thin-walled cortices. In the early Anisian (Lower Muschelkalk), small- and large-bodied Nothosaurus spp. generally exhibit bone mass increase (BMI). In the middle to late Anisian (Middle Muschelkalk) small-bodied nothosaurs retain BMI whereas larger-bodied forms tend to show a decrease in bone mass (BMD). During the latest Anisian to early Ladinian (Upper Muschelkalk), small- and few large-bodied nothosaurs retain BMI, whereas the majority of large-bodied forms exhibit BMD. The stratigraphically youngest nothosaurs document five microanatomical categories, two of which are unique among marine amniotes: One consists of a very heterogeneously distributed spongy periosteal organization, the other of very thin-walled cortices. The functional significance of the two unique microanatomical specializations seen in large-bodied nothosaurs is the reduction of bone mass, which minimizes inertia of the limbs, and thus saves energy during locomotion. Transitions between the various microanatomical categories are rather gradual. Our results suggest that small-bodied Nothosaurus marchicus and other, not further assignable small-bodied nothosaurs seem to have been bound to near-shore, shallow marine environments throughout their evolution. Some large-bodied Nothosaurus spp. followed the same trend but others became more active swimmers and possibly inhabited open marine environments. The variety of microanatomical patterns may be related to taxonomic differences, developmental plasticity, and possibly sexual dimorphism. Humeral microanatomy documents the diversification of nothosaur species into different environments to avoid intraclade competition as well as competition with other marine reptiles. Nothosaur microanatomy indicates that knowledge of processes involved in secondary aquatic adaptation and their interaction are more complex than previously believed.